A maturity model for curriculum management (2017)
In the academic context, a curriculum is mainly conceived as a process instead of as an object. For its design, it is possible to identify its maturity level to define the roadmap in which strategic practices that improve the whole teaching-learning process can be implemented. We propose a maturity model for curriculum management in higher education, based on curriculum design practices, the Feature Oriented Domain Analysis (FODA) approach, and IT support elements. As fundamentals, we are considering the phases of curriculum life cycle (design, reviewing, implementing, monitoring, and evolution) and the structural curriculum layers: macro curriculum, middle curriculum, and micro curriculum, for defining maturity levels by features, in people, processes, and tools dimensions. Copyright © 2017 Juan Bernardo Quintero and Bell Manrique-Losada:.